Numerical Solution of the Equation Modified Equal Width Equation by Using Cubic Trigonometric B-Spline Method - Salih, Hamad; Ridzuan Yahya, Zainor; Tawfiq, Luma; Mat Zin, Shazalina (International Journal of Engineering and Technology, 2018)
A numerical solution for the modified equal width was achieved via cubic trigonometric-B-spline (C. T.-B-spline) method approach which is based on finite difference scheme with the help of weighted scheme. In other words, the finite difference scheme is used to discretize the time derivative, while a cubic trigonometric B-spline is used as an interpolation map in the space dimension. The performance of the scheme was validated through two examination problems. The performance of the process was validated via using Â Â and Â Â error norms and conserved laws. Thus, stability analysis was applied by the von-Neumann method. Finally, the efficiency and accuracy of the suggested scheme was determined through comparison with the exact solution for different time and some other published numerical methods.Â